Development of sustainable self-compacting concrete using recycled concrete aggregate and fly ash, slag, silica fume. Issue 4 (12th March 2022) - Guo, Zhanggen; Zhang, Jing; Jiang, Tao; Jiang, Tianxun; Chen, Chen; Bo, Rui; Sun, Yan
Abstract: A sustainable Self-Compacting Concrete (SCC) was proposed by replacing natural aggregates with recycled coarse aggregates (RCAs) and cement with supplementary cementitious materials (SCMs). A total of 23 SCC mixes, including binary, ternary and quaternary mixes were prepared with three water to binder ratios (0.35, 0.40, and 0.45) and two RCA replacement levels (50%, 100%) as well as two SCM replacement levels (50%, 75%). The fresh state properties, in terms of filling ability, passing ability, viscosity and segregation resistance were studied as well as the hardened state properties. The effect of RCAs and SCMs on the fresh and hardened state properties of SCC mixes was analyzed as well as the influence of using a combination of fly ash, slag and/or silica fume. The test results indicate that SCC incorporating RCAs and SCMs exhibited superior workability and comparable compressive strength and the combination of fly ash, slag and silica fume can compensate for the detrimental effect of RCAs and increase the compressive strength. Thus, the content of RCAs and SCMs can be maximised by using a combination of fly ash, slag and silica fume, which will optimise the sustainability aspect of SCC mixes by minimising cement and nonrenewable natural resources content.